2011
DOI: 10.3855/jidc.1016
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibilities of enteric bacterial pathogens isolated in Kathmandu, Nepal, during 2002-2004

Abstract: Introduction: The prevalence and antimicrobial susceptibility patterns of the bacterial enteropathogens Vibrio cholerae, Salmonella species and Shigella species were investigated. Methodology: A total of 877 stool samples were received for culture at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
5
26
1
Order By: Relevance
“…Our results are in agreement with the findings of previous studies 19,20 . This might be due to the environmental and personal hygiene factors.…”
Section: Resultssupporting
confidence: 83%
“…Our results are in agreement with the findings of previous studies 19,20 . This might be due to the environmental and personal hygiene factors.…”
Section: Resultssupporting
confidence: 83%
“…are the most common agents of diarrhea (2,5,6). In spite of fluid and electrolyte replacement as a method of choice for the treatment of diarrheal diseases, antimicrobial therapy is recommended for suspected cases of Salmonella, Shigella and V. cholerae (7). The prescription of antibiotics for treatment of diarrheal diseases has a crucial role in reducing morbidity and mortality of the diseases; however, misuse and overuse of antibiotics in the treatment of diarrhea has resulted in antibiotic resistance (8).…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of these deaths are among children under two years of age. Predisposing factors such as malnutrition, low socioeconomic conditions, and poor hygiene are the major risk factors for such deaths in developing countries (3)(4)(5)(6)(7)(8). Among the bacteria responsible for diarrhea, Salmonella spp., Shigella spp., E. coli, Campylobacter spp., Vibrio cholerae, Aeromonas hydrophila, and Plesiomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…This study is in agreement with study done in Kathmandu in which most affected population was 20 to 29 yrs. 6 Similarly, in an outbreak study at Jajarkot, adult (15 to 44 yrs) were affected more. 3 However our study contrast with other studies which reported the prevalence of cholera in the children.…”
Section: Discussionmentioning
confidence: 99%